EKONOMI ISLAM MASA KINI: ANTARA REGULASI, GAYA HIDUP, DAN TEKNOLOGI SOSIAL - Muhammad Hafiz Zohri; Hilalludin Hilalludin (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
This study addresses the significant transformation of Islamic economics over the last two decades, highlighting its expansion from a financial system free of usury to a broader socio-economic phenomenon involving lifestyle, culture, and technological innovation. Unlike previous research that mainly focuses on formal Islamic finance institutions, this study examines the intersection of regulation, contemporary Muslim lifestyles, and social technology as key drivers shaping the current dynamics of Islamic economics. The motivation behind this research is to understand how these factors influence the authenticity and sustainability of Islamic economic practices amid globalization and digitalization. Using a qualitative approach through library research, this study critically reviews scholarly literature, regulatory documents, and social narratives to provide a comprehensive conceptual analysis. The findings reveal a complex interaction where regulatory frameworks often lag behind rapid societal changes, Muslim lifestyles sometimes emphasize symbolic consumption over substantive spiritual values, and technology presents both opportunities for inclusion and risks of commodifying religion. The study emphasizes the need for adaptive regulatory mechanisms grounded in maqashid shariah (objectives of Islamic law), enhanced digital literacy, and critical engagement with Muslim consumer culture. The policy implication is that Islamic economic development requires an integrative and interdisciplinary framework to ensure that economic activities truly reflect Islamic ethical principles and contribute to social justice, sustainability, and community welfare.